Single base substitution and insertion/deletion mutational signatures in adult core binding factor acute myeloid leukemia - Gunnarsson, Rebeqa; Yang, Minjun; Biloglav, andrea; Lazarevic, Vladimir; Paulsson, Kajsa; Johansson, Bertil (Lund University, 2022)
Paired diagnostic and remission samples from 20 adults with core binding factor acute myeloid leukemia (AML), comprising ten with t(8;21)(q22;q22) [RUNX1::RUNX1T1] and ten with inv(16)(p13q22)/t(16;16)(p13;q22) [CBFB::MYH11] analyzed by whole genome sequencing are included in this data set. All patients had de novo AML and the cases were selected based on the availability of good quality DNA from both diagnosis and remission. The median age of the patients was 51.5 years (range 19-74 years) and the female/male ratio was 1:1.5. the Declaration of Helsinki. DNA was extracted from diagnostic and remission bone marrow aspirates and sequencing libraries were constructed using the TruSeq PCR-Free DNA Library Preparation Kit (Illumina, San Diego, CA, USA) followed by cluster generation and 150 cycles paired-end sequencing with the NovaSeq 6000 system and v1.5 sequencing chemistry (Illumina) at the SNP&SEQ Technology Platform, Uppsala University. The data has been used for detection/investigation of single nucleotide variants, mutational signatures, fusion genes and copy number aberrations.
Keywords: Genomics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik